Two new planthopper species (Hemiptera, Fulgoroidea, Caliscelidae) collected in pitfall traps in Zambia - Chmurova, Lucia; Webb, Michael D. (Zootaxa, 2016)
Two new species of planthoppers in the family Caliscelidae (Hemiptera: Fulgoroidea) are described from Zambia, i.e., Afronaso spinosa sp. n. and Calampocus zambiaensis sp. n. All specimens are flightless males and nearly all were collected from baited pitfall traps (except for one specimen collected from a yellow pan trap), suggesting that they live near to or on the ground.